Forecasting life expectancy using latent and observable factors: effects of urbanization on mortality modelling - Norkhairunnisa Redzwan; Rozita Ramli (Penerbit Universiti Kebangsaan Malaysia, 2025)
Sustainable development of the future is influenced by population growth, population ageing, migration, and urbanization. However, urbanization have adverse effects on environmental, social behaviour and health aspects, such as mortality risks due to climate change and infectious diseases. As the urban population is growing rapidly, there is a need to accurately forecasts these risks in anticipation of future ageing population, by developing a model to estimate and forecast mortality. Many existing extrapolative mortality models are described by latent factors, and it is difficult to understand the underlying dynamics of these factors. Therefore, a comprehensive analysis on the relationship between mortality index and urbanization growth were conducted. This study also aims to propose a new model that incorporates urbanization as an observable factor in modelling and forecasting mortality, by extending the Lee-Carter model. Result indicates that there is a possible long-run relationship between mortality and growth of urban population for all countries in the study. The proposed model provides better in-sample fitting for all countries. This study also predicts the life expectancy at birth based on the proposed model and life expectancy is forecast to reach age 85 for selected countries. Results also show that Malaysian adults ages between 20 and 40 years old are more likely to be affected by an increase in urbanization growth. Urbanization and mortality are key factors in planning for sustainable development of the future. Therefore, it is important to develop a mortality forecasting model that can account for the uncertainty surrounding urbanization.